Gambaran Atribut Surveilans Campak di Wilayah Kerja Puskesmas Panglayungan Kota Tasikmalaya Tahun 2024 - Alika Arifiyani Ferbianti; Nazwa Salsabila; Putri Dzakiyya Lisdinawati; Siti Fatimah (Lembaga Pengembangan Kinerja Dosen, 2025)
Measles is one of the infectious diseases that continues to pose a challenge to public health in Indonesia. This study aims to evaluate the attributes of the measles surveillance system at Panglayungan Health Center, Tasikmalaya City, using a qualitative approach through interviews and the use of secondary data. The evaluation focused on nine key attributes of the surveillance system. The results showed that the system performed adequately in terms of simplicity, timeliness, acceptability, and data quality. However, weaknesses were identified in the attributes of flexibility, sensitivity, positive predictive value, and system stability, largely due to limitations in individual data and technical constraints. Therefore, improvements to the system can be made through strengthening information technology, training for health workers, and active community involvement in case reporting. An optimal surveillance system is essential for early detection and control of measles to reduce incidence and mortality, particularly in children under five years of age.